Efficacy of glecaprevir and pibrentasvir treatment for genotype 1b hepatitis C virus drug resistance-associated variants in humanized mice. (14th June 2019) - Osawa, Mitsutaka; Uchida, Takuro; Imamura, Michio; Teraoka, Yuji; Fujino, Hatsue; Nakahara, Takashi; Ono, Atsushi; Murakami, Eisuke; Kawaoka, Tomokazu; Miki, Daiki; Tsuge, Masataka; Hiramatsu, Akira; et al.
Abstract : Combination therapy with glecaprevir (GLE) and pibrentasvir (PIB) has high efficacy for pan-genotypic hepatitis C virus (HCV)-infected patients. However, the efficacy for patients who acquired potent NS5A inhibitor resistance-associated variants (RAVs) as a result of failure to respond to previous direct-acting antiviral (DAA) therapies is unclear. We investigated the efficacy of GLE/PIB treatment for genotype 1b HCV strains containing RAVs using subgenomic replicon systems and human hepatocyte transplanted mice. Mice were injected with serum samples obtained from a DAA-naïve patient or daclatasvir plus asunaprevir (DCV/ASV) treatment failures including NS5A-L31M/Y93H, -P58S/A92K or -P32 deletion (P32del) RAVs, then treated with GLE/PIB. HCV was eliminated by GLE/PIB treatment in mice with wild-type and NS5A-L31M/Y93H but relapsed in mice with NS5A-P58S/A92K, followed by emergence of additional NS5A mutations after cessation of the treatment. In NS5A-P32del-infected mice, serum HCV RNA remained positive during the GLE/PIB treatment. NS5A-P58S/A92K showed 1.5-fold resistance to PIB relative to wild-type based on analysis using HCV subgenomic replicon systems. When mice were administered various proportions of HCV wild-type and P32del strains and treated with GLE/PIB, serum HCV RNA remained positive in mice with high frequencies of P32del. In these mice, the P32del was undetectable by deep sequencing before GLE/PIB treatment, but P32del strains relapsed after cessation of the GLE/PIB treatment. GLE/PIB is effective for wild-type and NS5A-L31M/Y93H HCV strains, but the effect seems to be low for P58S/A92K and NS5A-P32del RAVs. Although NS5A-P32del was not detected, the mutation may be present at low frequency in DCV/ASV treatment failures.